2012
DOI: 10.2298/bah1203441s
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the relative bioavailability of several zinc sources for broilers when fed a conventional diet

Abstract: An experiment was conducted with 312 day-old male broiler chicks in grower phase(8-28d) to estimate the biological availability of four sources Zinc (Zn), Zinc sulfate(ZnSO 4. H 2 O), two sources of Zinc oxide(ZnO FG1 and ZnO FG2) and Bioplex Zn. Zinc sulfate (ZnSO 4. H 2 O) was used as the standard in the bioavailability assay. Chicks were allotted randomly to 13 dietary treatments with 6 birds per replicate and 4 replicates per treatment, that included an unsupplemented corn-soybean meal basal diet (25.50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The FCR result of present study was in line with Sahraei et al [13]. They used different sources of zinc and observed bioavailability and result concluded that feed conversion ratio was improved.…”
Section: Discussionsupporting
confidence: 89%
“…The FCR result of present study was in line with Sahraei et al [13]. They used different sources of zinc and observed bioavailability and result concluded that feed conversion ratio was improved.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the physiological and productive effects of various Zn sources in poultry diets have been extensively researched and reviewed in recent years (Naz et al, 2016;Abd El-Hack et al, 2017;Jankowski et al, 2019a, b). According to many authors, Zn deficiency is associated with reduced appetite, slower growth rate, skin abnormalities, poor feathering, decreased collagen production and long bone malformation (Park et al, 2004;Petrovič et al, 2011;Brooks et al, 2013;Sahraei et al, 2013;Ramiah et al, 2019).…”
mentioning
confidence: 99%